The analysis of burned human remains - Schmidt, Christopher W.; Symes, Steve A. (Elsevier/Academic, 2008)
This unique reference provides a primary source for osteologists and the medical/legal commumity for the understanding of burned bone remains in forensic or archaeological contexts. It describes in detail the changes in human bone and soft tissues as a body burns at both the chemical and gross levels and provides an overview of the current procedures in burned bone study. Case studies in forensic and archaeological settings aid those interested in the analysis of burned human bodies, from death scene investigators, to biological anthropologists looking at the recent or ancient dead. * Includes the diagnostic patterning of color changes that give insight to the severity of burning, the positioning of the body, and presence (or absence) of soft tissues during the burning event * Chapters on bones and teeth give step-by-step recommendations for how to study and recognize burned hard tissues.